Financial literacy: Social environment, self-control, and Tamansiswa “Tri-Nga” teachings on student financial behavior - Prastyatini, Sri Lestari Yuli; Utami, Regita Ummi Ashari Cahya (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the influence of the social environment, self-control, and Tamansiswa “Tri-Nga” teachings on students’ financial behavior with financial literacy as a moderating variable. This type of research is quantitative using a questionnaire as an instrument for collecting data. The population of this research is Accounting Students at Universities in Yogyakarta in 2019-2023. The total sample was 100 students using convenience sampling. The data analysis used was multiple linear regression tests and MRA. The results of the research prove that there is a positive and significant influence of the social environment on student financial behavior. Self-control has a positive and significant effect on students’ financial behavior. Tamansiswa’s teachings “Tri-Nga” have a positive and significant effect on students’ financial behavior. The MRA test output shows that financial literacy can strengthen the influence of the social environment and the Tamansiswa “Tri-Nga” teachings on students’ financial behavior. However, financial literacy cannot strengthen the influence of self-control on students’ financial behavior.